Strategi Pembentukan Karakter Religius di Lembaga Kesejahteraan Sosial Anak (LKSA) Panti Asuhan Muhammadiyah Tuksono Kulonprogo - Yogi Gunawan; Syamsudin Syamsudin (Yayasan Azhar Amanaa Yogyakarta, 2023)
The main objective of this study is to investigate and analyze the strategies and execution of religious character development at the Muhammadiyah Orphanage Center in Tuksono. This research utilized a qualitative approach through field research, with the participation of the Muhammadiyah Branch Leader, Chairperson, Management Committee, Caregivers, and orphanage residents as the respondents. The data was collected through observation, interviews, and documentation, and analyzed using descriptive-qualitative techniques along with interactive analysis. The research findings reveal that the orphanage employs various approaches in cultivating religious character, such as providing religious education through a madrasah diniyah, encouraging religious activities, and implementing rules and regulations. The implementation of these strategies has proven to be successful in shaping the religious character of the residents at the Muhammadiyah Orphanage Center in Tuksono. Despite encountering challenges such as a shortage of competent teachers, the diverse backgrounds of the residents, inactivity within the management committee, and interactions with the external community, the orphanage has effectively achieved its objectives by fostering the character development of the residents through collaborative efforts and the enforcement of rules.